A tool for assessing the sensitivity of soil-based approaches for quantifying enhanced weathering: a US case study - Suhrhoff, Tim Jesper; Reershemius, Tom; Wang, Jiuyuan; Jordan, Jacob S.; Reinhard, Christopher T.; Planavsky, Noah J. (Frontiers in Climate, 2024)
Enhanced weathering (EW) of silicate rocks spread onto managed lands as agricultural amendments is a promising carbon dioxide removal (CDR) approach. However, there is an obvious need for the development of tools for Measurement, Reporting, and Verification (MRV) before EW can be brought to scale. Shifts in the concentration of mobile elements measured in the solid phase of soils after application of EW feedstocks can potentially be used to track weathering and provide an estimate of the initial carbon dioxide removal of the system. To measure feedstock dissolution accurately it is necessary to control for the amount of feedstock originally present in the sample being analyzed. This can be achieved by measuring the concentration of immobile detrital elements in soil samples after feedstock addition. However, the resolvability of a signal using a soil mass balance approach depends on analytical uncertainty, the ability to accurately sample soils, the amount of feedstock relative to the amount of initial soil in a sample, and on the fraction of feedstock that has dissolved. Here, we assess the viability of soil-based mass-balance approaches across different settings. Specifically, we define a metric for tracer-specific resolvability of feedstock mass addition (φ) and calculate the feedstock application rates (a) and dissolution fractions (b) required to resolve EW. Applying calculations of a, b, and φ to a gridded soil database from the contiguous USA in combination with known compositions of basalt and peridotite feedstocks demonstrates the importance of adequately capturing field heterogeneity in soil elemental concentrations. While EW signals should be resolvable after ~1-3 years of basalt feedstock addition at common application rates for most agricultural settings with adequate sampling protocols, resolving EW in the field is likely to be challenging if uncertainties in tracer concentrations derived from field-scale heterogeneity and analytical error exceed 10%. Building from this framework, we also present a simple tool for practitioners to use to assess the viability of carrying out soil-based EW MRV in a deployment-specific context.